CHARACTER DEVELOPMENT TROUGH PHYSICAL EDUCATION: AN INDONESIAN PERSPECTIVE - Dimyati, D (Universitas Pendidikan Indonesia, 2023)
Concerned with many of the abuses ascribed to students and athletes, an increasing number of administrators, physical educators, coaches, and observers of sports believe that it has the potential to shape character. The potential impact of sports and physical education on character development is discussed in program administration and teaching/coaching behavior. Specific practices such as conditional scholarships, non-graduation of athletes, gender bias, modeling, drill, explanation and demonstration, encouraging athletes to play when injured,